2001
DOI: 10.1021/np000620d
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Inhibitory Effects of Naturally Occurring and Modified Fatty Acids

Abstract: In the search for new cyclooxygenase-2 (COX-2) selective inhibitors, the inhibitory effects of naturally occurring fatty acids and some of their structural derivatives on COX-2-catalyzed prostaglandin biosynthesis were investigated. Among these fatty acids, linoleic acid (LA), alpha-linolenic acid (alpha-LNA), myristic acid, and palmitic acid were isolated from a CH(2)Cl(2) extract of the plant Plantago major by bioassay-guided fractionation. Inhibitory effects of other natural, structurally related fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
1
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(138 citation statements)
references
References 29 publications
12
119
1
5
Order By: Relevance
“…Based on our test results for the COX-1 and COX-2 inhibitory activities of pure linoleic, oleic and stearic acids [69], [78] as well as the values reported by other groups [104], [105], it appears that fatty acids with higher unsaturation values possess more potent activity against COX-1 and COX-2 than their saturated analogues. Furthermore, the unsaturated fatty acids are selectively active against COX-2 [69], [78], [104], [105]. For example, the initial petroleum ether extract of the stems of Macrococculus pomiferus was found to significantly inhibit COX-2 (the % inhibition was 86 for both extracts at 100 mg/mL) [75].…”
Section: Inhibitory Activity On Cyclooxygenases-1 and -2 By Fatty Acidssupporting
confidence: 71%
See 2 more Smart Citations
“…Based on our test results for the COX-1 and COX-2 inhibitory activities of pure linoleic, oleic and stearic acids [69], [78] as well as the values reported by other groups [104], [105], it appears that fatty acids with higher unsaturation values possess more potent activity against COX-1 and COX-2 than their saturated analogues. Furthermore, the unsaturated fatty acids are selectively active against COX-2 [69], [78], [104], [105]. For example, the initial petroleum ether extract of the stems of Macrococculus pomiferus was found to significantly inhibit COX-2 (the % inhibition was 86 for both extracts at 100 mg/mL) [75].…”
Section: Inhibitory Activity On Cyclooxygenases-1 and -2 By Fatty Acidssupporting
confidence: 71%
“…However, the methylation product of the fatty acid mixture was inactive in these assays [78]. Based on our test results for the COX-1 and COX-2 inhibitory activities of pure linoleic, oleic and stearic acids [69], [78] as well as the values reported by other groups [104], [105], it appears that fatty acids with higher unsaturation values possess more potent activity against COX-1 and COX-2 than their saturated analogues. Furthermore, the unsaturated fatty acids are selectively active against COX-2 [69], [78], [104], [105].…”
Section: Inhibitory Activity On Cyclooxygenases-1 and -2 By Fatty Acidssupporting
confidence: 57%
See 1 more Smart Citation
“…The production of endometrial series 2 prostaglandins is mainly governed by the rate-limiting enzyme cyclooxygenase (COX)-2, which mediates embryo implantation in the mouse (Lim et al, 1999;Huang, 2008). The most potent COX-2 inhibitor is an omega 3 FA, eicosapentanoic acid (Ringbom et al, 2001). In a recent study, we have shown that the expression of different genes involved in the establishment of pregnancy in embryo and endometrial tissue is strongly modified by the supply of omega 3 FA in the diet (Palin et al, 2005).…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 99%
“…It has been shown to be a potent inhibitor of cyclooxiginase-2 (COX-2) catalyzed prostaglandin biosynthesis. 29,30 Among the other fatty acids with concentrations more than 1% are: Palmitic acid (6.59%), Oleic acid (5.41%) and Stearic acid (1.35%) were found. Amount of rest of the fatty acids were less than 1% (Table 1).…”
Section: Introductionmentioning
confidence: 98%